Development of immunity-related adverse events correlates with baseline clinical factors, survival and response to anti-PD-1 treatment in patients with inoperable or metastatic melanoma. (19th May 2022) - Cybulska-Stopa, Bożena; Ziętek, Marcin; Czarnecka, Anna M.; Piejko, Karolina; Dziura, Robert; Galus, Łukasz; Ziółkowska, Barbara; Kieszko, Stanisław; Kempa-Kamińska, Natasza; Calik, Jacek; Seredyńska, Joanna; Gądek, Kamila; et al.
Abstract: Background: The relationship between immune related adverse events (irAEs) and efficacy is not definitively proven, and data on the relationship between irAE and treatment efficacy are contradictory. Material and methods: Five hundred ninety-three consecutive patients with unresectable or metastatic melanoma treated in the first line with anti-PD-1 (nivolumab or pembrolizumab) between January 2016 and December 2019 were enrolled in the study. Results: Statistically significant differences were demonstrated between the group of patients without and with irAE in median OS and PFS ( p  < .0001 both) and also in OS between the group of patients without irAE and patients with irAE within 3, 6, and 9 months from the start of anti-PD-1 therapy ( p  = .0121, p  = .0014, p  < .0001; respectively) and PFS ( p  = .0369, p  = .0052, p  = .0001; respectively). A statistically significant relationship was demonstrated between the occurrence of irAE and the location of the primary tumor (skin vs. mucosa vs. unknown; p  = .0183), brain metastasis (present vs. absent; p  = .0032), other locations (present vs. absent, p  = .0032), LDH (normal vs. elevated; p  = .0046) and stage according to TNM ( p  = .0093). Conclusion: The occurrence of irAE was associated with longer OS, PFS, and more frequent response to treatment. IrAE occurred statistically significantly more often in patients with mucosa primary tumor, with normal LDH levels, without brain metastases, stages III, M1a, and M1b.